The influence of religious beliefs on gen Z’s intentions to choose Islamic higher education - Maulida Dwi Agustiningsih; Muhammad Ardy Zaini; Novita Nurul Islami; M. Khusna Amal; Rizki Alif Setyawan (Nur Science Institute, 2026)
Perguruan Tinggi Keagamaan Islam (PTKI) plays a vital role not only as centers for religious moderation but also in producing graduates who become community leaders contributing to national and religious development. This study aims to examine the factors influencing Generation Z’s intention to enrol in PTKI, with a focus on UIN Kiai Haji Achmad Siddiq Jember as a case study. The research specifically investigates whether religiosity, along with attitude, subjective norms, and perceived behavioral control, affects students' enrollment decisions. A quantitative approach was employed using a structured questionnaire to 168 high school students in the Tapal Kuda region (Jember, Banyuwangi, Lumajang, Bondowoso, Pasuruan, Situbondo, and Probolinggo). The data were analyzed using Structural Equation Modeling Partial Least Squares. The results indicate that attitude, subjective norms, and perceived behavioral control positively and significantly influence students’ intention to enrol, with attitude being the most dominant factor. In contrast, religiosity does not significantly impact enrollment decisions. These findings suggest that PTKI should focus their promotional and communication strategies on academic quality, professional prospects, and social influence rather than relying solely on religious orientation to attract prospective students.